Analisis Pemanfaatan Games dalam Meningkatkan Hasil Belajar Siswa dalam Pembelajaran PKn di SDN 2 Rantepao Toraja Utara - Salo, Eky Setiawan; Salu, Benyamin (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This fictitious qualitative research article analyzes the utilization of games in Civics education (PKn) at SDN 2 Rantepao, North Toraja, and its impact on students’ learning outcomes. The study involved 30 fifth-grade students. Data were collected through semi-structured interviews with students and the teacher, as well as direct observation of Civics lessons using game-based media. Thematic analysis was applied to identify emerging themes from the data. Results indicate that implementing educational games in PKn lessons enhanced students’ motivation, engagement, and conceptual understanding. Most students showed positive attitudes, became more active in asking questions, and collaborated more when learning with games. These findings align with previous studies suggesting that game-based learning creates interactive and enjoyable learning experiences, thereby increasing students’ engagement and motivation. In conclusion, integrating game media into PKn instruction at SDN 2 Rantepao is an effective alternative to improve learning outcomes and student interest, with recommendations for further development and teacher training in using interactive learning media.